The Impact of Microenvironment and Dysplasia Types on the Prognosis of Myelodysplastic Syndrome - Irem Guvendir Bakkaloglu; Itir Ebru Zemheri; Ali Hakan Kaya; Emrah Kilicaslan (Diagnostics)
Background: A detailed examination of bone marrow (BM) aspiration and biopsy can provide clues regarding the course of the disease as well as the diagnostic features of myelodysplastic syndrome (MDS). Methods: Our aim is to reveal the histomorphological features of MDS, investigate the impact of dysplasia types on prognosis, and highlight the importance of the microenvironment. Results: In 130 (93.5%) of 139 cases, Wright–Giemsa-stained BM aspiration slides were evaluated, and the dysplasia diversity was examined in detail. A regression analysis of dysplasia features significant for overall survival revealed that the presence of hyperlobulation in the megakaryocytic series (p = 0.014, odds ratio = 3.485) and the presence of an abnormal localization of immature progenitors (ALIP) (p = 0.010, odds ratio = 2.206) were significantly associated with poor prognosis. Additionally, an increase in the microvessel density (MVD) was found to be associated with a poor prognosis (p < 0.001). A multiple regression analysis identified that MVD is the most significant parameter (p = 0.014). Conclusions: The diversity of dysplasia in BM aspiration and biopsy does not predict MDS subtypes; however, certain cytomorphological dysplasia types can provide insights regarding survival. The microenvironment’s impact on MDS pathogenesis is undeniable, with ALIP and MVD presence and frequency being significant factors. Thus, BM histomorphological examination, beyond its diagnostic role, also offers prognostic insights